Stanisław Przybyszewski: In and Out of Pop Culture - Goławska-Stachowiak, Karolina (Zagadnienia Rodzajów Literackich, 2020)
Stanisław Przybyszewski’s oeuvre is not “pop”. This paper scrutinizes a catalogue of determinants that encouraged the writer’s initial renown and then led to his ultimate decline in popularity. Was Przybyszewski’s “fall from grace” justifiable? In my analysis, I refer to three different approaches to the concept of “pop”. In the first approach, “pop” is understood as a contrast between high and low culture. In the second, it is interpreted in relation to the institutions that indirectly affirm and popularize one’s literary input. The third one is associated with source literary text editing. Using these three categories is not supposed to present the author himself, but rather a certain phenomenon in European literary culture. Przybyszewski, the so-called “meteor of the Young Poland period”, is a particularly poignant example of how initial fascination with an avant-garde artist could change into oblivion and absence in reading culture. The comments formulated in this article are directed primarily to the reader who does not know the history of Polish literature, and the method of reaching the reader is to focus on a selected example showing a repeatable sequence in careers of many other authors of the period.